Co-sedimentation of kaolinite-montmorillonite suspensions - Szántó Ferenc (Acta mineralogica-petrographica, 1980)
The sedimentation of kaolinite and quartz prepared from flecked kaolin was investigated in a suspension made from the montmorillonite fraction as a medium. The concentration of the suspension the pH and the quantities of certain electrolytes (NaCI-and CaCl2) were varied, and it was found that the character of the complex sedimentation and the structures of the sediments are influenced to a great extent by these parameters. The (aggregated) cosedimentation of montmorillonite and kaolinite coiild be achieved when a kaolinite suspension coagulated to some extent was added to a stable montmorillonite suspension of appropriate concentration.